Serologic evidence of HoBi-like virus circulation in Argentinean water buffalo - Pecora, Andrea (2017)
Fil: Pecora, Andrea. Instituto Nacional de Tecnología Agropecuaria. Instituto de Investigación Virología; Argentina.